Literature Review: Characteristics of Hypertensive Patients at Community Health Centers - Dwiki Darmawan, Muhammad; Juanda, Trisnawati Wilhelmina; Fahik, Yuliana; Rosalina, Rosalina (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Hypertension is a degenerative disease that has become a global health problem with a high prevalence, particularly among adults and the elderly. This study aims to identify the characteristics of patients with hypertension at Community Health Centers (Puskesmas) through a literature review method. Article searches were conducted using the PubMed and Google Scholar databases with the keywords hypertension, characteristics, and Puskesmas. The inclusion criteria were studies published within the last five years, written in Indonesian and English, and focusing on the characteristics of hypertensive patients at Puskesmas. A total of 10 articles were analyzed in this review. The results show that hypertensive patients are predominantly female, aged ≥45 years, especially 46–65 years, with employment status as housewives or unemployed, and with low to moderate levels of education and low socioeconomic status. The most common risk factors include obesity, physical inactivity, unhealthy dietary patterns, family history of hypertension, and smoking habits. In conclusion, hypertension is a multifactorial disease influenced by both modifiable and non-modifiable risk factors. Therefore, promotive and preventive efforts are needed through health education, early detection, and the adoption of a healthy lifestyle to reduce the risk of hypertension in the community. Support from health policies and the enhanced role of healthcare workers are essential to strengthen the prevention and control of hypertension at the primary healthcare level in a sustainable manner across the population.